Retrospective overview of a COVID-19 outbreak in Mauritania. (November 2020) - El Vally, A.; Bollahi, M.A.; Ould Ahmedou Salem, M.S.; Deida, J.; Parola, P.; Basco, L.; El Bara, A.; ouldabdallahi, M.; Ould Mohamed Salem Boukhary, A.
Abstract: A coronavirus disease 2019 (COVID-19) outbreak is currently ongoing in Mauritania. Until 1 July 2020, Mauritania health authorities reported 41 862 serologic and real-time reverse transcriptase PCR tests performed, of which 4472 (10.7%) were positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Male subjects were significantly more affected (57.1%) than female subjects (42.9%). Individuals of the age groups 15–34 years (35.8%) and 35–54 years (36.6%) were the most affected. There were 129 deaths (2.9%), 1677 recoveries (37.5%) and 2666 active cases (59.6%) of which 2261 (84.8%) were asymptomatic, 394 (14.7%) had mild symptoms and 11 (0.4%) had severe symptoms. A large proportion of fatalities (72%, 85/118) occurred among adults aged ≥55 years. Of 4472 positive cases, 4241 (94.8%) were infected through contact with a confirmed COVID-19 case, 133 (3.0%) had no contact with a confirmed COVID-19 case and 98 (2.2%) were imported. As a response to COVID-19, the Mauritanian authorities announced a set of preventive measures, including closure of land and air borders, night curfew, closure of markets, schools and universities and restriction of movement between cities. Control measures included the systematic testing of symptomatic patients, isolation and management of active cases, contact tracing and quarantine of people who have been in contact with a COVID-19–positive individual. We discuss the efforts of the Mauritanian government to combat this potentially life-threatening pneumonia.